Regulation of HIF: prolyl hydroxylases. - Stolze, I; Mole, D; Ratcliffe, P (2006)
Hypoxia inducible factor (HIF) is an alpha/beta heterodimeric transcriptional complex that plays a key role in directing cellular responses to hypoxia. Recent studies have defined novel oxygen-sensitive signal pathways that regulate the activity of HIF by post-translational hydroxylation at specific residues within the alpha subunits. HIF prolyl hydroxylation regulates proteolytic degradation of HIF whereas HIF asparaginyl hydroxylation modulates interaction with transcriptional co-activators. These hydroxylations are catalysed by a set of non-haem Fe(II)- and 2-oxoglutarate (2-OG)-dependent dioxygenases. During catalysis, the splitting of molecular oxygen is coupled to the hydroxylation of HIF and the oxidative decarboxylation of 2-OG to give succinate and CO2. Hydroxylation at two prolyl residues within the central 'degradation domain' of HIF-alpha increases the affinity for the von Hippel-Lindau (pVHL) E3 ligase complex by at least three orders of magnitude, thus directing HIF-alpha polypeptides for proteolytic destruction by the ubiquitin/proteasome pathway. Since the HIF hydroxylases have an absolute requirement for molecular oxygen this process is suppressed in hypoxia allowing the HIF-alpha to escape destruction and activate transcription. Co-substrate and co-factor requirements for Fe(II), ascorbate, and the Krebs cycle intermediate 2-OG, and inducible changes in the cellular abundance of three closely related HIF prolyl hydroxylases (PHD1-3) provide additional interfaces with cellular oxygen status that may be important in regulating the oxygen-sensitive signal.